The Effectiveness of Use of Messenger as a Supportive Strategy in Teaching for Developing Academic Intrinsic Motivation and Academic Achievement - Heilat, Mustafa Qaseem; Almatarneh, Mansour Hussein (Dirasat: Educational Sciences, 2020)
This study aims to investigate the effectiveness of communication through Messenger for developing academic intrinsic motivation and academic achievement. To achieve the objectives of the study, an experimental method was used, and a scale of academic intrinsic motivation and academic achievement tests for the course of Drama and Theater in Education were used. The two tests (questionnaire and exams) were applied as pre-tests on all the control and the experimental groups. Communication through the messenger was applied on the experimental group. After completing this procedure, the two tests where applied again on all groups as post-tests. The study sample was divided into two groups; they consisted of 23 and 17 female students for the control and the experimental groups, respectively, during the academic year 2017/2018. The results showed that there were significant differences (p < 0.05) in the mean score of the participants’ performance on the academic intrinsic motivation, and on the academic achievement exams between control and experimental groups. It can be concluded that the experimental group performed better for academic intrinsic motivation and academic achievement compared with the control group. The adoption and utilization of the use of communication though messenger is highly recommended because of its effectiveness.